Prokaryotic gene expression - Baumberg, S. (Frontiers in molecular biology ;, 1999)
Prokaryotic gene expression is not only of theoretical interest but also of highly practical significance. It has implications for other biological problems, such as developmental biology and cancer, brings insights into genetic engineering and expression systems, and has consequences for important aspects of applied research. For example, the molecular basis of bacterial pathogenicity has implications for new antibiotics and in crop development. Prokaryotic Gene; Expression is a major review of the subject, providing up-to-date coverage as well as numerous insights by the prestigious authors. Topics covered include operons; protein recognition of sequence specific DNA- and RNA-binding sites; promoters; sigma factors, and variant tRNA polymerases; repressors and activators;; post-transcriptional control and attenuation; ribonuclease activity, mRNA stability, and translational repression; prokaryotic DNA topology, topoisomerases, and gene expression; regulatory networks, regulatory cascades and signal transduction; phosphotransfer reactions; switch systems, transcriptional and translational modulation, methylation, and recombination mechanisms; pathogenicity, toxin regulation and virulence determinants; sporulation and genetic regulation of antibiotic production;; origins of regulatory molecules, selective pressures and evolution of prokaryotic regulatory mechanisms systems. Over 1100 references to the primary literature are cited. Prokaryotic Gene Expression is a comprehensive and authoritative review of current knowledge and research in the area. It is; essential reading for postgraduates and researchers in the field. Advanced undergraduates in biochemistry, molecular biology, and microbiology will also find this book useful.